Species of the subgenus Neohomoneura van der Wulp from Hainan in China (Diptera, Lauxaniidae) - Shi, Li; Yang, Ding (Zootaxa, 2008)
The following five species of the subgenus Neohomoneura from Hainan are described as new to science: Homoneura (Neohomoneura) digitata sp. nov., H. (N.) tortilis sp. nov., H. (N.) tricuspidata sp. nov., H. (N.) tripetata sp. nov. and H. (N.) zengae sp. nov. Homoneura (Neohomoneura) pollex Sasakawa is newly recorded from China, and H. (N.) nadaensis Yang, Hu & Zhu is supplemented by male’s characters. A key to the species of the subgenus Neohomoneura from Hainan is presented.